GLOBALIZING WORLD AND THE RUSSIAN FEDERATION - Starostenkov, (Revista Inclusiones, 2020)
The study investigates the impact of globalization on social processes in the Russian Federation, studies the structure of the global economy and its impact on the economic development of countries, and assesses the prospects for the Russian Federation to occupy a decent position in the modern system of division of labour in the sphere of high technologies. Several problems are formulated due to the current model of globalization.